A={5,6} , B={4,5,6},C={5,6,7}, show that A×A=(B×B)n(C×C).
Answers
Answered by
4
Answer:
We are given
A={1,2,3,4,5,6}; B={4,6,7,8,9,10}
C={4,6,10,12}
(1) proof:
LHS=A u (B n C)={1,2,3,4,5,6} u [{4,6,7,8,9,10} n {4,6,10,12}]
= {1,2,3,4,5,6} u {4,6,10}
={1,2,3,4,5,6,10}------------(1)
RHS= (A u B) n (A u C)
=[{1,2,3,4,5,6} u {4,6,7,8,9,10}] n [{1,2,3,4,5,6} u {4,6,10,12}]
={1,2,3,4,5,6,7,8,9,10} n {1,2,3,4,5,6,10,12}
={1,2,3,4,5,6,10}--------------(2)
LHS=RHS
(2)
LHS=A U (B U C)
.={1,2,3,4,5,6} U [{4,6,7,8,9,10} U {4,6,10,12}]
={1,2,3,4,5,6} U {4,6,7,8,9,10,12}
={1,2,3,4,5,6,7,8,9,10,12}--------------(1)
RHS=(A U B) U (A U C)
=[{1,2,3,4,5,6} U {4,6,7,8,9,10}] U [{1,2,3,4,5,6} U {4,6,10,12}]
={1,2,3,4,5,6,7,8,9,10} U {1,2,3,4,5,6,10,12}
={1,2,3,4,5,6,7,8,9,10,12}-------------(2)
LHS=RHS
Answered by
23
Hope my attachment helps you...✌️✌️
Attachments:
![](https://hi-static.z-dn.net/files/dd3/9d2d1a98befe0380b40b5d15bb88b5a8.jpg)
![](https://hi-static.z-dn.net/files/dea/db8e15f9d29d6a11a4f37f67434b4e48.jpg)
Similar questions